The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/nano.202300100
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli‐responsive hydrogel microgels on porous silicon one‐dimensional photonic crystals: Tapping the full potential for optical sensor applications

Ruth Fabiola Balderas Valadez,
Augusto David Ariza Flores,
Claudia Pacholski

Abstract: Porous silicon 1D photonic crystals, namely rugate filters, are covered with a loosely packed hexagonally ordered array of stimuli‐responsive hydrogel microgels, and the optical properties of the resulting hybrid sensor are thoroughly investigated. For this purpose, both rugate filters with and without hydrogel microgel on top are immersed in ethanol/water mixtures possessing different compositions and NaCl solutions. Reflectance spectra of all samples are taken and analyzed concerning the spectral positions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…Next, Pacholski and colleagues fabricated a hybrid sensor made of photonic rugate filters obtained by wet electrochemical etching of silicon and covered them with a stimuli-responsive hydrogel microgels [27]. The authors then demonstrated the potential for developing optical sensors that can detect simultaneously and independently two parameters-the refractive index of the immersion medium and the swelling or collapse of hydrogel microgels.…”
Section: Areas Covered In the Special Topicmentioning
confidence: 99%
“…Next, Pacholski and colleagues fabricated a hybrid sensor made of photonic rugate filters obtained by wet electrochemical etching of silicon and covered them with a stimuli-responsive hydrogel microgels [27]. The authors then demonstrated the potential for developing optical sensors that can detect simultaneously and independently two parameters-the refractive index of the immersion medium and the swelling or collapse of hydrogel microgels.…”
Section: Areas Covered In the Special Topicmentioning
confidence: 99%